Humour strategies in teaching Chinese as second language classrooms. (July 2020) - Tong, Peiru; Tsung, Linda
Abstract: Recent research has shown that teachers who are positive, humorous, happy, well-organised, supportive, and respectful of students are appreciated by their students (Jiang & Dewaele, 2019). This paper aims to explore humour strategies in the classroom of Chinese as a second language (L2) in an in-country study (ICS) program. In particular the study aims to answer three questions: (1) Was humour a common phenomenon in the Chinese language classrooms? (2) How was humorous classroom discourse constructed? (3) How did the humour strategies promote language learning and use? Qualitative data were collected through class observations and student interviews. The study has identified naturally occurring data to explore the phenomenon of humour. The findings indicate that humour strategies in the L2 classroom not only helped students challenge their stereotypical impressions of Chinese educational culture but also facilitated their language use and learning motivation. Chinese teachers are suggested to consider incorporating humour strategically in their teaching, which may contribute to learners' long-term desire for language learning and ICS in China.